Audio Visual Aids-Quality Use in Lecture Classes of Undergraduate Medical Education in Bangladesh (Medicine Today, 2017)
This descriptive type of cross sectional study was conducted to explore the use of AV aids in undergraduate medical education in 7 government & 5 non-government medical colleges of Bangladesh by convenient sampling. Sixty (60) lecture classes were observed to estimate the proportion of the uses of different AV aids & to identify the quality use of different types of AV aids by observation checklists. Views were also taken from 20 teachers regarding the quality use of different types of AV aids by open ended questions. Study revealed that 20% teachers used CB/WB, 15% used OHP and 65% used PPT. Most of the CB/WB & PPT users maintained the quality use of these media but not OHP. Readability and legibility of handwriting or text of all media were acceptable in 78% lectures but it was 33% in OHP lectures. Students' attention was also less in OHP. Regarding number of words per acetate sheet/slide, only 33% OHP lectures met the standard criteria & 72% PPT slides met this criterion. In open ended questions, 25% teachers choose CB/WB, 10% Choose OHP and 65% choose PPT. Study recommended that use of clean, multi-color and good quality chalk/marker & board/screen are essential for effective teaching learning session. Adequate lighting, AC lecture class/gallery, proper sound systems & training on different AV aids are also needed to standardize the quality use of AV aids in lecture classes.Medicine Today 2016 Vol.28(2): 48-51